2020
DOI: 10.1016/j.ejmp.2019.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Segmentation of organs-at-risk in cervical cancer CT images with a convolutional neural network

Abstract: We introduced and evaluated an end-to-end organs-at-risk (OARs) segmentation model that can provide accurate and consistent OARs segmentation results in much less time. Methods: We collected 105 patients' Computed Tomography (CT) scans that diagnosed locally advanced cervical cancer and treated with radiotherapy in one hospital. Seven organs, including the bladder, bone marrow, left femoral head, right femoral head, rectum, small intestine and spinal cord were defined as OARs. The annotated contours of the OAR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
80
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(91 citation statements)
references
References 57 publications
6
80
0
1
Order By: Relevance
“…Previous studies on auto-segmentation, using different systems, have shown moderate to high levels of overlap (as measured with the Dice score). The segmentation of femoral heads is highly concordant in general according to previous literature, with a Dice score range of 90-95% [15,16,[27][28][29]), which is in line with the results in this present study (median: 0.91-0.94). The reason for this high overlap is probably the femoral heads having good contrast with the surrounding tissue and often being regular with a well-defined shape.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Previous studies on auto-segmentation, using different systems, have shown moderate to high levels of overlap (as measured with the Dice score). The segmentation of femoral heads is highly concordant in general according to previous literature, with a Dice score range of 90-95% [15,16,[27][28][29]), which is in line with the results in this present study (median: 0.91-0.94). The reason for this high overlap is probably the femoral heads having good contrast with the surrounding tissue and often being regular with a well-defined shape.…”
Section: Discussionsupporting
confidence: 92%
“…In the case of rectal cancer, a previous study evaluated the auto-segmentation of target volume and OAR, and showed varying segmentation accuracy based on the Dice similarity coefficient ranging from 61.8% (colon) to 93.4% (bladder) [15]. Recently on cervical cancer, Liu et al [16] described a method for OAR (but not CTVN) segmentation using CNNs, with structure sets as ground truth. Their method used a modified version of 2D U-Net, hence not fully utilizing the 3D nature of the data.…”
Section: Introductionmentioning
confidence: 99%
“…The number of training, validation, and test CT scans we used to train and evaluate this model is the largest to date among deep learning-based female pelvis auto-contouring studies. 25,26 We successfully acquired this high volume of data by using a semi-automatic data curation method. Also, to the best of our knowledge, we are the first to auto-contour nodal and PAN CTVs in the female pelvic region using deep learning.…”
Section: Discussionmentioning
confidence: 99%
“…We have developed a CNN‐based auto‐contouring tool for three CTVs and 11 normal structures in cervical cancer CTs that can be used for fully automated radiation treatment planning. The number of training, validation, and test CT scans we used to train and evaluate this model is the largest to date among deep learning‐based female pelvis auto‐contouring studies 25,26 . We successfully acquired this high volume of data by using a semi‐automatic data curation method.…”
Section: Discussionmentioning
confidence: 99%
“…OARs delineation is a key step before radiotherapy planning. Precise treatment delivery relies heavily on accurate OARs delineation (38). At present, there have been many researches on automatic heart segmentation, but most of them are carried out on high-quality and well-displayed images such as MRI and CTA (39)(40)(41)(42).This research is carried out on radiotherapy positioning CT, which is the basic image of clinical radiotherapy.…”
Section: Discussionmentioning
confidence: 99%